BIOMECHANICAL AND BIOCHEMICAL WEATHERING OF LICHEN-ENCRUSTED GRANITE: TEXTURAL CONTROLS ON ORGANIC-MINERAL INTERACTIONS AND DEPOSITION OF SILICA-RICH LAYERS - Lee M.R.; Parsons I. (My University, 1999)
The crustose lichen Rhizocarpon geographicum weathers the Lower Devonian Shap Granite by both biomechanical and biochemical means. Biomechanical weathering is mediated by fungal hyphae that penetrate into the rock via intergranular boundaries at =<0.002-0.003 mm year-1. Once inside the granite, hyphae exploit intragranular pores along cleavage and fracture planes in biotite, alkali and plagioclase feldspar. Grains of biotite exposed at the lichen-granite interface have been fragmented by biomechanical action in <122 years. After an extended period of biomechanical weathering of <10 kyr outcrop surfaces, sub-mm sized fragments of biotite and plagioclase feldspar abound in lower parts of the lichen's thallus. Grains of biomechanically weathered biotite show the clearest evidence for biochemical weathering. Typically, K and Fe are leached from the biotite, but other cations may also be removed, leaving a silica-dominated relic. The silica-rich remains of biotite and possibly also feldspar have been redistributed along the lichen-granite interface forming a silica-rich layer. This silica-rich material also cements fractures and pores beneath the interface. Alkali feldspars from outcrop surfaces have been weathered chemically, as indicated by etch pits on cleavage surfaces and fractures, but it is not obvious that lichen was involved in the dissolution. The etch pits were probably formed during earlier phases of non-biochemical weathering that widened intergranular and intragranular pores, facilitating subsequent access of fungal hyphae into the granite. Despite evidence for biomechanical and biochemical weathering, it is unlikely that colonisation of granite surfaces by R. geographicum at Shap significantly enhances their weathering rate relative to bare rock surfaces. The lichen may actually retard weathering by protecting the surface from frost action, binding fragmented mineral grains and depositing `protective' silica-rich layers.
Keywords: LICHEN; BIOMECHANICAL WEATHERING; BIOCHEMICAL WEATHERING; BIOTITE; FELDSPAR